2009
DOI: 10.1523/jneurosci.0208-09.2009
|View full text |Cite
|
Sign up to set email alerts
|

Cochlear Damage Changes the Distribution of Vesicular Glutamate Transporters Associated with Auditory and Nonauditory Inputs to the Cochlear Nucleus

Abstract: Integration of multimodal information is essential for understanding complex environments. In the auditory system, multisensory integration first occurs in the cochlear nucleus (CN), where auditory nerve and somatosensory pathways converge (Shore, 2005). A unique feature of multisensory neurons is their propensity to receive cross-modal compensation following deafening. Based on our findings that the vesicular glutamate transporters, VGLUT1 and VGLUT2, are differentially associated with auditory nerve and soma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

17
151
3
1

Year Published

2011
2011
2012
2012

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(172 citation statements)
references
References 58 publications
17
151
3
1
Order By: Relevance
“…Finally, our studies indicate that no changes in excitatory neurotransmission mediate enhanced signals in tinnitus mice. Although previous studies have suggested that an increase in excitatory inputs in the DCN after noise damage could lead to hyperactivity (15), our study provides an experimental test of the role of excitation and inhibition in the same animals with behavioral evidence of tinnitus.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Finally, our studies indicate that no changes in excitatory neurotransmission mediate enhanced signals in tinnitus mice. Although previous studies have suggested that an increase in excitatory inputs in the DCN after noise damage could lead to hyperactivity (15), our study provides an experimental test of the role of excitation and inhibition in the same animals with behavioral evidence of tinnitus.…”
Section: Discussionmentioning
confidence: 86%
“…However, direct evidence that disinhibition mediates these changes is still lacking. In addition, the alternative hypothesis that predicts increased excitation as a potential mechanism in mediating these changes has not been tested (15). Addressing these unexamined questions could lead to pharmacological approaches for treating tinnitus patients.…”
mentioning
confidence: 99%
“…The greater wave III/I and V/I amplitude ratios of tinnitus subjects compared with matched non-tinnitus subjects could arise in a variety of ways including via (1) alterations in the membrane properties of neurons in the SBC pathway leading to their greater excitability, (2) diminished inhibition of the SBC pathway from descending projections, or possibly, (3) synaptic remodeling (Kim et al 2004;Zeng et al 2009;or lack thereof, Kraus et al 2011). Recent neurophysiological data in animals supports the presence of increased SBC excitability following acoustic trauma, a common cause of tinnitus (Vogler et al 2011).…”
Section: Ventral Cochlear Nucleus and Tinnitusmentioning
confidence: 99%
“…At the same time, there is evidence for increased excitation in some areas. For example, the decline in glutamatergic input, presumably from primary afferents following noise exposure, is eventually followed by increases in glutamatergic neurotransmission in the cochlear nucleus, superior olivary complex, and IC (Potashner et al 1997;Shore 2011;Zeng et al 2009Zeng et al , 2011. There is also evidence for an upregulation of cholinergic inputs to the cochlear nucleus following noise exposure and cochlear ablation (Chang et al 2002;Jin and Godfrey 2006;Jin et al 2006;Kaltenbach and Zhang 2006).…”
mentioning
confidence: 99%
“…We sought, in particular, to determine whether hyperactivity in the IC is dependent on inputs from the DCN. The relationship between these nuclei is particularly well suited for this study because previous studies have shown that hyperactivity in the DCN is generated by the major output neurons, the fusiform cells (Brozoski et al 2002;Finlayson and Kaltenbach 2009;Zeng et al 2009), which are primary sources of input to the contralateral IC. Moreover, tinnitus demonstrated using behavioral testing methods has been found to be correlated with increases in bursting and/or nonbursting spontaneous activity of DCN fusiform cells (Brozoski et al 2002;Finlayson and Kaltenbach 2009;Kaltenbach et al 2004) and sizeable populations of neurons in the IC (Bauer et al 2008).…”
mentioning
confidence: 99%